2003
DOI: 10.1111/j.1553-2712.2003.tb02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Care in the Emergency Department: Should Emergency Departments Conduct Routine HIV Screening? A Systematic Review

Abstract: Multiple ED-based studies meeting the Centers for Disease Control and Prevention Guideline threshold to recommend routine screening, in conjunction with limited feasibility trials and extrapolation from cost-benefit studies, provide evidence to recommend that EDs offer HIV screening to high-risk patients (i.e., those with identifiable risk factors) or high-risk populations (i.e., those where HIV seroprevelance is at least 1%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…A major obstacle to such analyses in the current study and previous reports is the lack of clinical outcomes data for various prevention activities in the ED setting. 20 Although economic estimates from other settings are available, we suggest the need for ED-specific outcomes investigation.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…A major obstacle to such analyses in the current study and previous reports is the lack of clinical outcomes data for various prevention activities in the ED setting. 20 Although economic estimates from other settings are available, we suggest the need for ED-specific outcomes investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Multiple possibilities to provide the resources needed for ED-based HIV testing have been proposed. 20 Our program is novel in its collaboration with a local health department for program operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of studies of prevalence of undiagnosed HIV in ED patients found a range of 1% to 5%. 9 The CDC recommends routine counseling, testing, and referral for HIV at sites, such as EDs, that offer HIV testing for patients with risk factors or for patient populations that have an HIV prevalence greater than 1%. 10 If the prevalence of HIV infection in a setting is less than 1%, then testing should be offered to high-risk populations, such as men who have sex with men, persons seeking treatment for sexually transmitted diseases, intravenous drug users and their partners, patients who had transfusion of blood products between 1978 and 1985, and persons who have had multiple sex partners or who exchanged sex for money or drugs.…”
Section: D C U P D a T Ementioning
confidence: 99%